Men in family care practices: documentary analysis of Brazilian theses and dissertations (Research, Society and Development, 2020)
This paper aims to analyze the trend of scientific productions of Brazilian graduate programs about the experience of men as responsible for care in the family. This is a documentary study conducted in the Thesis Database of the Higher Education Personnel Improvement Coordination, in June 2018. The search for the documents was performed using the strategy “(experience OR experience OR experience) AND (man OR men OR male OR masculinities) AND care ”. After applying the selection criteria, seven documents comprised the corpus of analysis. Of the analyzed documents, five were dissertations and two theses, developed in the areas of nursing, psychology, psychosociology, public health and social work, developed in institutions in the South and Southeast region, in 2013, with a qualitative approach. The themes addressed involved the experience and / or experience of men in caring for themselves and others, in the face of aging or illness, sharing care for children or adolescents in chronic situations, care for children or women in psychological distress. It was identified as a tendency that studies involving men in the practice of care address the actions that they perform for the care of their own health, their children or their partner. It is identified a gap in scientific knowledge regarding the amount of studies aimed at men as being active in the process of caring for the illness of a family member or close person.